Plan de negocios para la exportación vehículos de tracción humana hacia Montreal (Canadá) (2015)
TRIKE.CO SAS, seeking to enter the market in Montreal - Canada, with a product that allows consumers to give an alternative transport at low cost and in less time to mobilize, with an added value that is to protect the environment. This product is a human-powered vehicle (tricycle) designed for a person with an average weight of 60-100 kg. Montreal - Canada, is the largest city in the province of Quebec, in Canada and the second most populous country. It is also an administrative region of Quebec. It is situated on the island of the same name in the St. Lawrence River and Rivière des Prairies. It is a major industrial, commercial and cultural centers of North America. Montreal has 4'027.100 inhabitants, continental climate is humid and road infrastructure is far-reaching because it has a subway and public transportation system integrated. It also has bike paths and trails suitable for cycling and use VTH as a means of sustainable transport. Making it the first city in the Americas in the use of this means of transport.